Assessment of Modified RELAP5 MOD3.2 Against LBE Natural Circulation Test Loops - Lv, Yufeng; Liu, Xingmin; Li, Weihan; Guo, Chunqiu; Zhou, Zhiwei (Frontiers in Energy Research, 2021)
The system analysis computer code RELAP5 MOD3.2 was developed for thermal hydraulic study of light water reactor as well as non-nuclear loop-type system using water as coolant. The purpose of this work is to modify the code for system analysis of Lead Bismuth Eutectic (LBE) cooled fast reactor (LFR) and non-nuclear systems. The thermo-physical properties of LBE together with the heat transfer correlations for liquid metal were incorporated into the RELAP5 MOD3.2 code. The methods of code modifications are universal for other working fluids and will not affect the code original performance．The validation of the modified RELAP5 code was done in comparison with test results from two different test facilities. The first one is Natural Circulation Experimental (NACIE) facility performed by ENEA and the results of test number 21 at power of 22.5 kW was taken for comparison. The simulated profiles of temperatures, mass flow rate of LBE agree well with the test data. The other test is from Natural Circulation Capability Loop (NCCL) facility conducted by Xi'an Jiaotong University. Five different power levels (4.5kW, 5.8kW, 7.5kW, 9.8kW and 15kW) under natural circulation conditions are considered. Results obtained for LBE mass flow rate and temperature difference were compared with code predictions. The results show that the calculation results are in consistent with the experimental data. The capability and reliability of the modified RELAP5 code has been demonstrated for further analysis of LFRs.